2021
DOI: 10.32598/bcn.12.2.986.1
|View full text |Cite
|
Sign up to set email alerts
|

Hippocampal Astrocyte Response to Melatonin Following Neural Damage Induction in Rats

Abstract: Introduction: Brain injury induces an almost immediate response from glial cells, especially astrocytes. Activation of astrocytes leads to the production of inflammatory cytokines and reactive oxygen species that may result in secondary neuronal damage. Melatonin is an anti-inflammatory and antioxidant agent, and it has been reported to exert neuroprotection through the prevention of neuronal death in several models of central nervous system injury. This study aimed to investigate the effect of melatonin on as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…The protective effect of melatonin on the brain neurons and oligodendrocytes in demyelinating pathology is associated with its anti-inflammatory, anti-apoptotic and antioxidant effects ( Vakilzadeh et al, 2016 ; Babaee et al, 2021 ; Murioz-Jurado et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The protective effect of melatonin on the brain neurons and oligodendrocytes in demyelinating pathology is associated with its anti-inflammatory, anti-apoptotic and antioxidant effects ( Vakilzadeh et al, 2016 ; Babaee et al, 2021 ; Murioz-Jurado et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…The anti-inflammatory effect of melatonin is manifested in the inhibition of activation of NF-κB in cells, resulting to a decrease: (a) the synthesis of inflammatory mediators; (b) the level of adhesive molecules ICAM-1 and VCAM-1; (c) the production of pro-inflammatory cytokines (TNF-α, IL-1β, IFN-γ, IL-17, and IL-22) by T lymphocytes, macrophages and astrocytes and to The number of GM-CFCs in bone marrow and the blood level of monocytes in young and aging mice of experimental groups. an increase the production of anti-inflammatory cytokines (IL-10 and IL-4) (Escribano et al, 2014;Alvarez-Sanchez et al, 2015, 2017Farez et al, 2015;Xu et al, 2018;Babaee et al, 2021;Murioz-Jurado et al, 2022). Under melatonin influence activity of T-helpers, T-effectors, T-regulatory cells changes and the differentiation of Th17 inhibits in animals with an experimental model of multiple sclerosis (Alvarez-Sanchez et al, 2015;Farez et al, 2015).…”
Section: Neuroinflammatory Cellsmentioning
confidence: 99%
“…It has been shown that MT production is not associated with the photoperiodic environment, while changes in MT subcellular distribution are due to specifics of their metabolic activity and the formation of toxic oxygen derivatives [9]. The increased MT synthesis and discharge in the brain in the case of acute hypoxia and traumatic brain injury in humans [41] are mediated by stress in which MT acts as a potent neuroprotector and antioxidant [42]. In cultivated neural stem cells from the subventricular zone of adult mice, researchers found a large amount of MT, and its production was even higher when these cells differentiated into mature neurons.…”
Section: Melatonin In the Nervous Systemmentioning
confidence: 99%
“…As described above, activated astrocytes lead to the production of inflammatory cytokines and ROSs, which may contribute to secondary neuronal injury. Melatonin treatment after brain injury reduces astrocyte reactivity and cell death in a dose-independent pattern in rat hippocampus and dentate gyrus ( Babaee et al, 2021 ). In addition, melatonin treatment significantly abolished the effects of LPS-induced inflammation, as indicated by decreased cytokine (TNFα, IL-1β, IL-6) and inhibition of NF-κB phosphorylation ( Ali et al, 2020 ).…”
Section: Circadian Involved In Inflammatory Response After Ischemic S...mentioning
confidence: 99%